Novel Protein Kinase Induced during Sporangial Cleavage in the Oomycete Phytophthora infestans - Judelson, Howard S. (American Society for Microbiology, 2002)
A study of the effect of inhibitors on zoospore development in Phytophthora infestans demonstrated the involvement of protein kinases and calcium and led to the discovery of a gene induced during zoosporogenesis that encoded a protein resembling Ca(+2)- and calmodulin-regulated serine/threonine protein kinases. The calcium channel blocker verapamil and the calmodulin antagonist trifluoroperazine inhibited zoosporogenesis and encystment. The protein kinase inhibitors K-252a and KN-93 inhibited zoospore release, encystment, and cyst germination, and K-252a reduced zoospore viability. In contrast, the inhibitors had minor or no effects on sporangia directly germinating in media. Spurred by these findings, a survey of putative protein kinase genes was performed to identify any that were up-regulated during zoosporogenesis. A kinase-encoding gene was identified for which mRNA accumulation was first detected soon after chilling sporangia in water, conditions that induce sporangial cytoplasm to cleave and release zoospores. The transcript persisted in motile zoospores and in germinated cysts but was not detected in other tissues, including hyphae, hyphae placed in water, or directly germinating sporangia. The structure of the predicted protein was novel, as its C-terminal region, which binds calmodulin in related proteins, was unusually short. Concentrations of actinomycin D previously used in experiments that suggested that de novo transcription was not needed for zoosporogenesis or encystment only partially inhibited transcription of the kinase gene, probably due to poor uptake into sporangia.